SIKAP METRO TV DALAM PERSAINGAN PASAR OLIGOPOLI - Robbikal Muntaha Meliala (Jurnal Akrab Juara, 2018)
One of the biggest 13 conglomerates that she mentioned in her researched is Media Group. Media Group was known as partisan media by public which famous profile of owner is Surya Paloh, leader of National Democrat Party (Nasdem). Metro TV as one of sub-unit business of Media group strictly consistent with its vision to be â€œNews of Television Stationâ€ in embracing the competition. Then, providing its news by 3 languages, they are Indonesia, English and Mandarin. Target audience from this television station is high class with segmentation male or female, type of AB, 20 years old above, and has content 70% of hard news and 30% of entertainment program. Metro TV still keep their broadcasting quality within 24 hours by 75%-85% concept of in-house production, focus on news and life style program with educative packaging and luxurius audio visual program. Research Methodology: Descriptive Qualitative by Observations, Interviews, Study of Literature and Documentation. Summary:Today, Metro TV highly focuses on Economic News, Entrepreneur Program and Governmentâ€™s Supporter TV Station of Joko Widodoâ€™s Leadership. Keywords : Mass Media, Metro TV, Oligopoly Market